PRAKTIKALITAS MEDIA PEMBELAJARAN BERBASIS STEM PADA MATERI FLUIDA DINAMIS SMA - Annisa Arrahma; Fakhruddin Fakhruddin; Nur Islami (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research aim to verify the practicality of learning media in dynamic fluid material which contains of experimental tools and students’ worksheet in Bernoulli’s law and the principal of continuity. Before the test of practicality, these experimental tools and students’ worksheet have been avowed valid of 3 validators which are physic education experts. Research approach that has been used is development research with ADDIE model. The research data came from practicality experimental tools and students’ worksheet questionnaire and analyzed by Ms. Excel. The respondents are 3 teachers and 10 students as the practitioners. The result is, practicality test based on teachers in average 3.39 for experimental tools and 3.38 for dynamic fluid experiment students’ worksheet. While based on students, the results in average 3.42 for experimental tools and 3.46 for dynamic fluid experiment students’ worksheet. At the same time, the average value of learning media practicality based on STEM in dynamic fluid material is at 3.41. Based on those data, learning media based on STEM in dynamic fluid material can be stated practical with high category.Key Words: Practicality Test, Learning Media, ADDIE